Index-based livestock insurance for Kenyan pastoralists: An innovation systems perspective - Matsaert, H.; Kariuki, Juliet B.; Mude, Andrew G. (Informa UK Limited, 2011)
Pastoralists in northern Kenya live with a high level of risk, including climatic shocks, disease, and insecurity. This article considers the potential role of index-based livestock insurance (IBLI) as a mechanism which pastoralists can use to manage climate-related risk. How might it complement or compete with existing risk-management practices? Is the current institutional and policy environment favourable to developing this type of product? This study uses an innovation systems perspective to explore and answer some of these questions, and to consider the strategic role of research and development actors in the development process.